PENGARUH MODEL PROJECT-BASED LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS V SEKOLAH DASAR - Yurma Vadelta; Erni; Niken Yuni Astiti; Fadhilah Khairani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem of low science learning outcomes at SD Negeri 01 Bukit Kemuning in science learning for grade V is the main focus of this study. This study aims to determine the effect of the Project-Based Learning Model on the Learning Outcomes of Grade V Students in the Science Subject of Elementary Schools. This study uses a quantitative approach with a quasi-experimental design method with a nonequivalent control group design. Determination of the research sample uses a non-probability sampling technique with a purposive sampling technique. The population in this study amounted to 75 students with the samples used being students in grades V A and V B. Data were collected using test and non-test techniques in the form of observation and documentation. Data were analyzed using a simple Linear Regression Test. The results of this study indicate that there is a significant influence on the application of the Project-Based Learning model on the learning outcomes of grade V students in the science subject of elementary school.